47. DETECTION OF BACTEROIDES FRAGILIS BACTERIA IN TUMORS OF COLORECTAL CANCER PATIENTS (Tạp chí Y học Cộng đồng, 2024)
Objective: To investigate the presence of Enterotoxigenic Bacteroides fragilis (ETBF) in colorectal cancer (CRC) patients in Vietnam.Methods: A cross-sectional descriptive study was conducted using molecular biology techniques and a convenience sampling method. The study included 123 patients diagnosed with colorectal cancer in 2023–2024 at Military Hospital 175, Vietnam.Results: Using a range of recombinant plasmid concentrations from 106 to 1 copy alongside DNA extracted from healthy human blood samples, the PCR method demonstrated detection sensitivity down to 10 bacterial copies per clinical sample. Optimized PCR conditions were applied to the 123 CRC samples, identifying B. fragilis in 82 samples, corresponding to a positivity rate of 66.7%. No correlation was observed between the presence of B. fragilis and patient characteristics such as age, sex, tumor differentiation, tumor location, or invasion depth.Conclusion: The positivity rate for Enterotoxigenic Bacteroides fragilis among CRC patients in Vietnam is relatively high. These findings suggest that microbiota alterations could have potential as a biomarker for early detection of colorectal cancer.
Keywords: Enterotoxigenic Bacteroides fragilis; CRC; PCR